Psychometric Evaluation of the Diabetes Distress Scale in Patients with Type 2 Diabetes in Turkey - Nurten Terkes (Ivano-Frankivsk National Medical University, 2021)
The objective of the research was to evaluate the validity and reliability of the Diabetes Distress Scale in patients with type 2 diabetes in Turkey.